The impact of government effectiveness on trade and financial openness: The generalized quantile panel regression approach - Lethiwe Nzama; Thanda Sithole; Sezer Bozkuş Kahyaoglu (Journal of Risk and Financial Management, 2023)
Purpose: This paper aims to investigate the impact of government effectiveness on trade and financial openness in 35 selected countries around the globe. Design/methodology/approach: A quantitative research approach was applied in the study using the generalized quantile panel regression approach to analyze the impact of identified variables in these selected countries. Panel quantile models with high estimation performance are preferred in the presence of excessive deviations and in cases where the normal distribution is invalid. Findings/results: The empirical findings indicate that selected countries with above-average governmental effectiveness, that is, with a well-established state bureaucracy and a historically strong state tradition, will further increase their activities toward international integration through financial and trade openness. Practical implications: This study aims to provide valuable information that governments and regulatory authorities can benefit from in their decision-making processes. Originality/value: In this study, it is preferred to use the trade openness of countries as the share of exports in total world exports and financial openness as the ratio of capital flows to world flows. In this way, these variables will provide new information to analyze the influence of government effectiveness. Implementing the generalized quantile panel regression technique can also be expressed as an innovation in this field of literature.
Keywords: 650; governance; financial openness; generalized quantile panel regression; government effectiveness; trade openness